Individualised dosing of anti-thymocyte globulin in paediatric unrelated allogeneic haematopoietic stem-cell transplantation (PARACHUTE): a single-arm, phase 2 clinical trial. Issue 2 (February 2022) - Admiraal, Rick; Nierkens, Stefan; Bierings, Marc B; Bredius, Robbert G M; van Vliet, Ineke; Jiang, Yilin; Lopez-Yurda, Marta; Versluijs, A Birgitta; Zwaan, C Michel; Lindemans, Caroline A; Boelens, Jaap Jan
Summary: Background: Anti-thymocyte globulin, which is used in the conditioning of haematopoietic stem-cell transplantation (HSCT) to prevent graft-versus-host disease (GVHD) and graft failure, has highly variable pharmacokinetics. Overexposure to anti-thymocyte globulin leads to poor CD4 + T-cell immune reconstitution, which is associated with inferior overall survival. We hypothesised that individualised anti-thymocyte globulin dosing would promote CD4 + immune reconstitution, while still preventing GVHD and graft failure. Methods: We report the results of a prospective, single-arm, phase 2 clinical trial done at the University Medical Center Utrecht and the Princess Máxima Center for Pediatric Oncology (Utrecht, Netherlands) to investigate individualised dosing of anti-thymocyte globulin for unrelated allogeneic HSCT in paediatric patients. Anti-thymocyte globulin dosing was based on bodyweight, absolute lymphocyte counts before the first dose, and the stem-cell source, with cumulative doses ranging from 2–10 mg/kg. Patients younger than 18 years receiving a first HSCT with a T-cell repleted graft for any indication and a Lansky/Karnofsky performance status of at least 70% were eligible for inclusion. The primary endpoint was CD4 + immune reconstitution (>0·05 × 10 9 CD4 + T-cells per L twice within 100 days [±3] after transplantation). The primary endpoint needed to be met in 38 of 53 evaluable patients (no death, relapse, or graft failure before day 100). Toxicity was registered according to Common Terminology Criteria for Adverse Events criteria version 4.0. The study is registered with the Dutch Trial Register, NL4836. Findings: Between July 1, 2015, and Aug 22, 2018, 58 patients were included in the study, of whom 51 were evaluable for the primary endpoint. Median follow-up was 25·6 months (IQR 15·0–37·0) and median age was 7·4 years (IQR 2·8–13·2). 29 (50%) of 58 patients were female. CD4 + immune reconstitution was reached in 41 (80%, 95% CI 67–90, in survival analysis) of 51 evaluable patients, hence the study met its primary endpoint. There was no difference in CD4 + immune reconstitution between patients who received different stem-cell sources (87% [95% CI 61–96] in cord blood, 77% [54–89] in bone marrow [p=0·62]). The most common grade 3–5 adverse events were infections (32 [50%] patients had grade 3, two [3%] patients had grade 4, and seven [11%] patients had fatal events) and immunological disorders (seven [11%] patients had grade 3, three [5%] patients had grade 4, and five [8%] patients had fatal events). Two (3%) of 64 patients died of GVHD, which might be indirectly related to the intervention. Interpretation: Individualised dosing of anti-thymocyte globulin led to a significant improvement in early CD4 + immune reconstitution without increasing GVHD and graft failure incidence. Promotion of early CD4 + immune reconstitution by individualising anti-thymocyte globulin dose might improve outcomes of allogeneic HSCT. Funding: Sanofi.